Interaction of thermal time and nitrogen levels on growth and productivity of cotton (Gossypium hirsutum) - PRAKASH, A H; BANDYOPADHYAY, K K; GOPALAKRISHNAN, N; KUMAR, ANDERSON AMALAN (The Indian Journal of Agricultural Sciences, 2010)
A field experiment was carried out at Coimbatore to study the interaction of date of sowing and N levels on growth, biomass partitioning and productivity of a popular ‘LRA 5166’ cotton (Gossypium hirsutum L.) under winter irrigated condition. The 8 August sown crop experienced the maximum cumulative growing degree days (1 560), whereas the 7 September sown crop experienced the minimum cumulative growing degree days (1489). The plant height and the number of sympodial branches decreased with the delay in sowing but increased with the increase in N levels. Nitrogen application improved the leaf area duration than the control and the maximum leaf area duration was recorded under 120 kg N/ha. Till 105 days after sowing, leaf was the major sink of photosynthates (28.8–38.1%), while seed cotton became the major sink of photosynthates after this period. There was significant decrease in the number of bolls/plant under late sowing (7 September) situation. However, with the increase in the N levels the number of bolls/plant increased significantly. Similar trend was observed with respect to seed cotton yield. Sowing of ‘LRA 5166’ can be delayed maximum up to 18 August which is the optimum time of sowing and sowing beyond this time leads to significant decline in seed cotton yield. The optimum dose of nitrogen for ‘LRA 5166’ was 60 kg N/ha for getting higher partial factor productivity of nitrogen but without significant yield reduction under the winter irrigated situation in Tamil Nadu.